2016
DOI: 10.1021/acs.analchem.6b03185
|View full text |Cite
|
Sign up to set email alerts
|

Pump- and Valve-Free Flow Injection Capillary Liquid Electrode Discharge Optical Emission Spectrometry Coupled to a Droplet Array Platform

Abstract: A miniature (2.5 cm length × 2.0 cm width × 1.0 cm height), low power (<10 W), and capillary liquid electrode microplasma optical emission spectrometer was developed for rapid determination of metallic species in aqueous solutions. The sample solution can be automatically introduced into the source without a pump owing to the inherent capillary attraction and the force arising from the solution vaporization induced by microplasma. A droplet array was used as a sampling platform to realize flow injection withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Furthermore, the careful operation of this device is required because it is not easy to absolutely prevent high voltage from travelling to the operation table and causing injury to the operator. In order to overcome these shortcomings, a silver film was deposited on the outer surface of the capillary via silver mirror reaction to allow the high voltage to directly conduct along the outer surface of the capillary to its end, thus eliminating the generation of bubbles in the capillary and improving the stability of the microplasma. Moreover, the silver film on the end of the capillary immersed into the sample solution was scraped off with a knife, which would significantly alleviate the risk of injury from electric shock to the operator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the careful operation of this device is required because it is not easy to absolutely prevent high voltage from travelling to the operation table and causing injury to the operator. In order to overcome these shortcomings, a silver film was deposited on the outer surface of the capillary via silver mirror reaction to allow the high voltage to directly conduct along the outer surface of the capillary to its end, thus eliminating the generation of bubbles in the capillary and improving the stability of the microplasma. Moreover, the silver film on the end of the capillary immersed into the sample solution was scraped off with a knife, which would significantly alleviate the risk of injury from electric shock to the operator.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, a pump- and valve-free flow injection capillary liquid electrode microdischarge (CLED) OES system has been developed for elemental analysis. , Owing to the capillary action and sample vaporization in the microplasma, the sample solution could be automatically introduced into the plasma to generate atomic emission lines of analytes. In this system, sample consumption could be accurately controlled by sampling time and reduced to the nanoliter level.…”
mentioning
confidence: 99%
“…On the other hand, although the considerable improvements of atomic spectrometry have been achieved and even permit directly reporting the content of toxic metals in natural water, their instrumentation is still too bulky, expensive, and gas- and power-consuming to be used for field analysis. Recently, many studies demonstrated that a miniature microplasma atomic spectrometer retains promising potential for the field analysis of toxic metals. , However, the low sensitivities of the microplasma atomic spectrometers limit the scope of elements amenable to detection. Interestingly, the use of SPME for sample introduction means miniaturized point discharge optical emission spectrometry (μPD-OES) could improve the detection limit at least 100-fold for Hg and Pb compared to other sampling techniques .…”
mentioning
confidence: 99%
“…The miniaturization efforts have only barely touched atomic spectrometry. Although a few papers appeared about miniaturized plasmas (inductively coupled plasma (ICP), capacitively coupled plasma (CCP), microwave-induced plasma (MIP), or dielectric barrier discharge (DBD) ) used for element-selective detection, those did not become widely used. In addition, the graphite furnace or flame techniques have not been transferred to microchip format and only a very few papers appeared about hyphenation of microchips with atomic spectrometers.…”
mentioning
confidence: 99%